Synthesis, Structure and Spectral Properties of Tetranuclear Zn(II) Complex Based on 2-Hydroxy-3-methoxybenzaldehyde - Wang, P.; Zhao, L. (Asian Journal of Chemistry, 2015)
A supramolecular tetranuclear Zn(II) complex, [(ZnL)2(AcO)2{Zn(EtOH)}2] (H3L = 6-methoxy-6'-hydroxy-2,2'-[ethylenediyldioxybis-(nitrilomethylidyne)]diphenol), has been synthesized and characterized structurally. The structure of the Zn(II) complex consists of four Zn(II) atoms, two tridentate L3- units, two acetate ions and two coordinated ethanol molecules. All of the Zn(II) ions in the Zn(II) complex are five-coordinated and have slightly distorted tetragonal pyramidal geometry and pentahedral geometry, respectively. Moreover, every Zn(II) complex molecule links other molecules into an infinite 3D supramolecular structure via intermolecular C-H···O interactions and C-H···p interactions.